The Study Of Effectiveness Of Seven-Step (7E) Teaching Method In The Progress Of English Learning In Students Shiraz City - Bozorgpouri, Morvarid (The Turkish Online Journal of Design Art and Communication, 2016)
This study aimed to investigate the effectiveness of learning English based on the cyclic model (7E). Accordingly, three language institutes in the Shiraz city were selected and among 203 students of these three institutions by calling 132 were registered as volunteers to participate in training classes. After the implementation 20 questions language standard test designed the researcher and with collaboration of teachers of these institutions 30 students who received a low score on this test were selected as examples. The selected sample was divided into two experimental and control groups by random assignment. Finally, 15 students were randomly assigned to the experimental group and 15 students in the control group. For experimental group seven-step teaching method (7E) was used, while traditional method with no resemblance to the seven-step teaching method (7E) was used for the control group. Teaching with seven-step teaching method (7E) during a month and in 3 sessions per week was performed. Finally, for 12 sessions training content through this teaching method was presented to students. After running the post- test data were collected and were analyzed by SPSS software. A significant difference was found between the mean of control group and experimental group in the pre-test and post-test and language scores with the mean of experimental group compared with the control group, about four score increased, which this increase was statistically significant at the level of 0/05 (p=0/001).
Keywords: seven-stage (7E) teaching method; Language students; Cooperative teaching; The Shiraz city